2007
DOI: 10.1259/bjr/20938070
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings of radiation-induced sarcoma of the head and neck

Abstract: We set out to retrospectively review the clinical and imaging features of patients with post-radiation sarcoma, especially in the head and neck region. We reviewed the records of 4194 patients with carcinoma of the head and neck region who had a history of radiation. They had undergone CT and/or MRI. Medical records were reviewed for the primary diagnosis, radiation history and latency period to the development of sarcoma. The patients included four men and two women with a mean age of 64.5 years. The mean lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 24 publications
3
41
0
Order By: Relevance
“…24 MFH has also been reported to occur secondary to irradiation, trauma, Paget disease, osteonecrosis, chronic osteomyelitis, and benign bone tumors such as enchondroma and giant cell tumor. 10,22,23,25 Compared with the tumors that arise de novo, secondary MFHs are reported to be more aggressive with a poorer prognosis. 8,22,24 Head and neck MFH can be confused with a variety of fibrous tumors and inflammatory conditions, including neurilemmoma, fibromatosis, premature sarcoma, hemangiopericytoma, granuloma, nodular fasciitis, malignant mesenchymal tumor, myoblastoma, fat necrosis, Langerhans cell histiocytosis, pleomorphic rhabdomyosarcoma, and fibrosarcoma.…”
Section: Figmentioning
confidence: 99%
“…24 MFH has also been reported to occur secondary to irradiation, trauma, Paget disease, osteonecrosis, chronic osteomyelitis, and benign bone tumors such as enchondroma and giant cell tumor. 10,22,23,25 Compared with the tumors that arise de novo, secondary MFHs are reported to be more aggressive with a poorer prognosis. 8,22,24 Head and neck MFH can be confused with a variety of fibrous tumors and inflammatory conditions, including neurilemmoma, fibromatosis, premature sarcoma, hemangiopericytoma, granuloma, nodular fasciitis, malignant mesenchymal tumor, myoblastoma, fat necrosis, Langerhans cell histiocytosis, pleomorphic rhabdomyosarcoma, and fibrosarcoma.…”
Section: Figmentioning
confidence: 99%
“…Radiation to the STSHN is also a risk factor. Makimoto et al reported, only six cases (0.14%) of 4184 patients were with a history of radiation, whereas Ko et al, found sarcoma in 0.38% of patients radiated and the most frequent subtype was histiofibrocytoma [15][16] . In our study we did not find any cases of sarcoma associated with radiation.…”
Section: Discussionmentioning
confidence: 98%
“…In terms of MR findings, some researchers have reported that osteosarcoma shows low signal intensity on T1W images and heterogeneous high signal intensity on T2W images 6,7) . In this case, the lesion showed low signal intensity on T1W images and a little heterogeneous high signal intensity on T2W images with fat-suppression, which is in agreement with these earlier findings.…”
Section: Discussionmentioning
confidence: 99%